Práticas pedagógicas na educação de jovens e adultos: uma experiência na escola Nossa Senhora do Perpétuo Socorro na comunidade quilombola Piratuba - PEREIRA, Maria das Graças da Silva (2019)
This work brings a survey conducted with the 1st Stage of Education of Young and Adult of the School Our Lady of Perpetual Help of the Community Quilombola Piratuba located in the PA, 150km from the municipality of Abaetetuba/Pa. It is a research that seeks to understand a little more about teaching that has been developed in this community. This research has as its object the pedagogical practices in the aforementioned class, whose general objective is to understand the pedagogical practice developed in the 1st Stage of the Education of Young and Adults of the School Our Lady of Perpetual Help of the Community Quilombola Piratuba located in the PA. Methodologically the research is based on the qualitative approach, where it was possible to go to the locus to understand the pedagogical practice developed by the titular teacher, it was also possible to carry out the practical activities with the students of the group of the 1st Stage of the EJA in a playful perspective with the objective of emphasizing the valorization and consolidation of the local culture. In this way, we believe that it is the most important research not only for personal reasons, but also because it gives us the opportunity to socialize knowledge and knowledge that leads us to reflect on this theme and its contextualization in the Amazon.